2000
DOI: 10.1007/s004680000055
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in wood density and radial growth of Quercus petraea Liebl. in northern France since the middle of the nineteenth century

Abstract: Long-term changes in sessile oak (Quercus petraea Liebl.) growth and wood density were studied using cores collected from 99 even-aged high forest stands between 56 and 187 years old, located in northeastern and north-central France. Growth and density trends were tested by analysis of variance and covariance. Two models were applied to two samples, sample A and sample B (sample B being a sub-sample with limited cambial age and calendar date ranges). Model 1 showed a significant increase in radial growth: +35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
45
2
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 32 publications
9
45
2
3
Order By: Relevance
“…These patterns corroborate the results of previous studies in other oaks i.e. in 70 -110-year-old Q. suber trees (Knapič et al, 2008), in 80-year-old Q. garryana (Lei et al, 1996), in 56 to 187-year-old Q. petraea (Bergès et al, 2000) as well as in other mature American oaks (Q. nigra, Q. rubra, Q. falcata, Q. velutina) (Paul, 2008). It is interesting to note that the average dbh of the studied trees is in line with Loewenstein et al (2000) age models for white oaks under a managed uneven-aged oak forest.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These patterns corroborate the results of previous studies in other oaks i.e. in 70 -110-year-old Q. suber trees (Knapič et al, 2008), in 80-year-old Q. garryana (Lei et al, 1996), in 56 to 187-year-old Q. petraea (Bergès et al, 2000) as well as in other mature American oaks (Q. nigra, Q. rubra, Q. falcata, Q. velutina) (Paul, 2008). It is interesting to note that the average dbh of the studied trees is in line with Loewenstein et al (2000) age models for white oaks under a managed uneven-aged oak forest.…”
Section: Discussionsupporting
confidence: 91%
“…(e.g. Lei et al, 1996;Bergès et al, 2000), the wood density range is quite diverse within this genus and there is little information on variation patterns in high density woods such as Q. faginea (Nepveu, 1984;Dilem, 1995;Woodcock & Shier, 2002). The knowledge obtained will be important broadly in the size-and age-related changes in hardwoods quality context, and locally for forest management of the actual Q. faginea stands targeted towards solid wood products, and for increasing the interest in the economic exploitation of this autochthonous species in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Our results are in contrast with those from temperate lowland oak forests of Belgium (Kint et al 2012) and France (Becker et al 1994, Bergès et al 2000 reporting increased growth rates. The first study attributed the increased oak growth to the increase of temperature in the growing season, the latter suggested a number of environmental changes in, inter alia, temperature regime, CO2 concentration, and N deposition as drivers of increased growth rates for both sessile and pedunculate oak in northern and northeastern France.…”
Section: Pedunculate Oakcontrasting
confidence: 99%
“…In contrast, Tegel et al (2014) reported on a recent growth increase of beech at its southeastern distribution limit at the Balkan Peninsula. Sessile and pedunculate oaks seem to have rising growth rates in recent decades in Germany and in northern and northeastern France, presumably driven by changes in temperature regime, CO2 concentration and N deposition (Becker et al 1994, Pretzsch 1996, Bergès et al 2000. While these retrospective studies give valuable indications for regional species-specific future growth developments, the direct impact of projected climate change scenarios on radial growth (i.e., tree-ring width) of Scots pine, common beech and pedunculate oak in central European lowland forests have not been assessed adequately so far.…”
Section: Introductionmentioning
confidence: 99%
“…Bergès et al (2000)e t Guilley (2000)o nt montréq uel adensité du bois de Chêne sessile était restée stable ou avait augmentéau cours du dernier siècle. Aucune donnée n'est encored isponible sur les changements éventuels de composition chimiqued u bois (taux de carbone, rapport cellulose/lignine…).…”
Section: Discussionunclassified